Manganese carbonyl induced cationic reversible addition–fragmentation chain transfer (C-RAFT) polymerization under visible light. Issue 15 (25th March 2020) - Li, Jiajia; Kerr, Andrew; Häkkinen, Satu; Floyd, Thomas; Zhang, Mengmeng; Pan, Xiangqiang; Zhu, Xiulin; Perrier, Sébastien; Zhu, Jian
Abstract : Vinyl ethers were polymerized by C-RAFT polymerization on the basis of halide abstraction reaction of manganese carbonyl and organic halide. Abstract : The manganese carbonyl induced cationic reversible addition–fragmentation chain transfer (C-RAFT) polymerization under mild conditions such as visible light, room temperature and even in the presence of small quantities of water is reported. In this method, halide abstraction reaction between organic halide and manganese carbonyl is used to generate the oxidant and initiate radicals. The C-RAFT agents are generated in situ from radical transfer reactions between vinyl ethers and three traditional RAFT agents including xanthate, trithiocarbonate and dithiocarbamate species. Poly(vinyl ether)s with RAFT agent terminated chain ends have been successfully obtained and used as macroRAFT agents for preparation of block copolymers combining RAFT radical polymerization. Poly(isobutyl vinyl ether)- b -poly(vinyl acetate) and poly(isobutyl vinyl ether)- b -poly(methyl acrylate) are successfully prepared. In addition, poly(butyl acrylate)- b -poly(isobutyl vinyl ether) have also been obtained using poly(butyl acrylate) prepared by RAFT radical polymerization as macroRAFT agent. Our results show that poly(vinyl ether)s with controlled molecular weight and narrow molecular weight distribution (<1.2) can be obtained when using dithiocarbamate.